A Longitudinal Approach to the Relationships Among Sleep, Behavioral Adjustment, and Maternal Depression in Preschoolers - Cha, Kijoo (Frontiers in Psychology, 2022)
This study aimed to investigate the longitudinal associations between children’s sleep duration (SD) and problems (SPs), behavioral adjustment (externalizing behaviors [EB] and internalizing behaviors [IB]), and maternal depressive symptoms (MDS) in preschoolers over a period of three years (four to six years of age). For this purpose, latent growth modeling was conducted using 2012(W5) to 2014(W7) data from the National Panel Study on Korean Children (PSKC), while controlling for family contextual factors (i.e., responsive parenting, developmental stimulations, and marital conflict) and child temperament (children’s negative emotionality). First, children who slept longer at four were concurrently associated with lower levels of EB, while more SPs were associated with higher levels of EB and IB, concurrently. Second, greater decreases in SPs were associated with greater decline in EB and IB. Higher levels of MDS at four were associated with higher levels of child EB, IB, and SPs, concurrently. However, no longitudinal associations were found between the rates of change in MDS and children’s sleep and adjustment (EB and IB). Finally, the magnitude of the associations among the variables was greater overall in the SPs models than in the SD models. These findings suggest that addressing sleep problems, rather than sleep duration, seem to be more important in predicting and preventing young children’s adjustment problems, and also that more attention should be paid to MDS during preschool years as much as during the postpartum period for better child adjustment outcomes.